Worse Preoperative Hearing Thresholds and Younger Patients in Tomographic Retrofenestral Otosclerosis. (2nd September 2014) - Palma, Camilo; Caro, Carlos Stott; Delano, Paul H.; Ojeda, Alejandro; Gonzalez, Gonzalo Miranda
Abstract : Objectives: Usually, the diagnosis of otosclerosis is based on clinical and audiometric findings, and its confirmation requires surgical exploration of the middle ear. More recently, it has been suggested that high‐resolution computed tomography of the temporal bone (TTB) could diagnose and classify otosclerosis into fenestra otosclerosis (FO) and retrofenestral or cochlear otosclerosis (RFO). However, there are relatively few studies that relate these tomographic features with clinical and surgical findings. The aims of the study were to: (1) classify otosclerosis patients with preoperative TTB into fenestra or retrofenestral otosclerosis, and (2) compare these image findings with pre‐ and postoperative auditory thresholds and epidemiological findings. Methods: Retrospective study by reviewing medical records of otosclerosis patients (2006‐2011) undergoing estapedostomy in the Clinical Hospital of the University of Chile (tertiary institution), who were evaluated with preoperative TTB and had full audiometric data. Descriptive statistics and t test or analysis of variance with Tukey post hoc test were used as necessary, considering a P value <.05 as significant. Results: A total of 74 estapedostomies from 56 patients were evaluated. The TTB study had 87% sensitivity for the surgical diagnosis of fenestral otosclerosis. Age and hearing thresholds were significantly lower in patients with tomographic RFO compared to FO otosclerosis ( t test, P <. 05). Conclusions: The TTB is a useful imaging method to classify otosclerosis patients into RFO and FO varieties. In addition, the RFO corresponds to a more aggressive variety of otosclerosis (younger patients and lower auditory thresholds), and thus this method may be used as a prognostic tool.